Performance Measurement of E-Commerce Utilization in MSMEs in Situbondo Regency - Dian Widiarti; Salya Rater; Zidane Aji Wijaya; Ahmat Muniril Ihsan (Jurnal Inotera, 2024)
The development of the digital is inseparable from the convenience factor and greater benefits that can be obtained by users. Likewise in the business, with the development of digital platforms for product marketing activities, it will also have an impact on micro and medium businesses. This study wants to find out whether it is true that the use of e-commerce can improve the performance of MSME businesses. Factors that influence such as how technology, organization and environment will impact the adoption of e-commerce itself which will ultimately affect business performance in this case the MSME business. This study is an explanatory research that explains the causal relationship (cause and effect) between variables using SEM / PLS analysis. The test results show that technology and the environment have a positive and significant effect on the adoption of e-commerce and the organization has a positive but not significant effect on the adoption of e-commerce. As an intervening variable, namely the adoption of technology, it is produced that technology and the environment affect the performance of MSMEs through the e-commerce adoption variable and the organization has a positive but not significant effect on the performance of MSMEs through the e-commerce adoption variable. The overall results can be concluded that the increase in MSME performance is significantly influenced by technological factors based on the convenience, usefulness and ability to use it. Environmental factors, especially consumer behavior in utilizing technology and trends in utilizing technology in the online shopping process, also have a significant influence on the adoption of the technology itself, thus impacting business performance.